Improvement of thermoplastic elastomer degradation resistance by low-energy plasma immersion ion bombardment - Resende, R. C. [UNESP]; Ribeiro, R. P. [UNESP]; Waldman, W. R.; Cruz, N. C. [UNESP]; Araujo, J. R.; Rangel, E. C. [UNESP] (Elsevier, 2020)
Thermoplastic elastomers (TPE) have been used instead of traditional elastomers, since they combine the low cost of raw material with easy processing and recyclability. When used in sealing components, the polyester-based TPE, or COPEs, are most common. Although COPEs have mechanical properties similar to those of elastomers, they have limited resistance to corrosion in chlorinated water. Argon Plasma Immersion Ion Implantation (IIIP) treatments were applied to alter the morphology and chemical composition of the COPE surface, with the goal of increasing its chemical inertia in chlorinated water while preserving the desired bulk properties. The effect of ion bombardment energy on the elemental composition, chemical structure, morphology, topography and mechanical properties of COPEs was evaluated, along with whether changes in such properties affected the degradation resistance of the material in chlorinated water. Treatments were performed for 60 min in radiofrequency argon plasmas (13.56 MHz, 5.0 Pa), with the power of the excitation signal varying from 10 to 150 W. Since variations in signal power changed the self-bias potential of the driven electrode, and samples were positioned at this electrode, the ion bombardment intensity was varied in the different treatments. Immediately after treatments, surfaces became more hydrophilic than the as-received ones, but after being aged in air, some samples became hydrophobic. Dehydrogenation was the main alteration attained in chemical composition, inducing changes in the overall chemical structure. Species removal from less resistant regions promoted creation of nanometric structures randomly distributed on the surface but without promoting changes in the volumetric mechanical properties of COPE. The most pronounced surface changes were observed for the sample treated in plasmas at 150 W, which also presented the highest resistance to chlorinated solution. This improvement suggests an increase in COPE performance in practice.
Keywords: Chlorine degradation; COPE; Plasma immersion ion implantation; Thermoplastic elastomer; Wettability